Assessment of knowledge, attitudes, and practices regarding cardiovascular diseases (CVDs) among older individuals of rural Bangladesh: findings from a face-to-face interview - Siddique, Abu Bakkar; Hosen, Md. Shohag; Akter, Hasna; Hossain, Syed Mujakkir; Al Mamun, Md. (Frontiers in Public Health, 2024)
Abstract Introduction: Cardiovascular diseases (CVDs) stand as the foremost contributor to global mortality, claiming roughly 17.9 million lives each year, constituting 32.1% of total fatalities. Their impact is notably profound in economies such as Bangladesh, exacting a substantial economic burden. Consequently, grasping the landscape of knowledge, attitudes, and practices is essential for timely identification and prevention strategies. Methods: This cross-sectional study, carried out between January and May 2023 in the rural regions of Zirani, Savar Upazila, Dhaka, Bangladesh, utilized convenient sampling and conducted face-to-face interviews using a semi-structured questionnaire. It encompassed socio-demographic factors, as well as knowledge, attitudes, and practices concerning CVDs. Data analysis employed descriptive statistics, chi-square tests, and regression analyses, utilizing both the R programming language and SPSS (Version 26). Result: A total of 424 participants aged 60 years and above were included. The majority were male (60.8%), and the mean age was 71.21±9.21 years, 57.3% were between 60 to 70 years old. Factors such as education, monthly family income, high blood pressure, diabetes, and non-smoking. were significantly associated with higher knowledge, attitudes and practices scores. Conclusion: This study illuminates CVD-related KAP among rural Older Individuals in Bangladesh, revealing significant associations between factors such as education, monthly family income, high blood pressure, and non-smoking, with higher scores in knowledge, attitudes, and practices regarding cardiovascular health. These insights underscore the importance of addressing socio-economic factors and health behaviors in developing targeted interventions for the prevention and management of cardiovascular diseases in this demographic.